Pendidikan Agama Islam dan Pengembangan Critical Thinking pada Siswa Sekolah Menengah - Harni Kadang; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
Islamic Religious Education (PAI) has a central role in shaping the character and mindset of students at the secondary school level. In the context of 21st century education, the development of critical thinking skills is an essential requirement to create a generation capable of facing global challenges. This literature study aims to analyze how PAI can contribute significantly to the development of critical thinking in secondary school students. This study uses a descriptive qualitative approach by reviewing various relevant journals, books, and scientific articles. The results of the study indicate that a dialogic, contextual, and problem-based PAI learning approach can stimulate students to think analytically, reflectively, and logically. Five important aspects in this discussion include the integration of Islamic values ​​in critical thinking, active learning methods, the role of teachers as facilitators, a classroom environment that supports discussion, and learning evaluations that challenge students' analytical abilities. Thus, PAI is not only a means of instilling spiritual values, but also a vehicle for forming critical and constructive mindsets. In conclusion, strengthening the PAI curriculum that supports the development of critical thinking is very important to create graduates who are religious and think rationally.